2008
DOI: 10.1007/s00114-008-0413-9
|View full text |Cite
|
Sign up to set email alerts
|

RNAi-mediated silencing of vitellogenin gene function turns honeybee (Apis mellifera) workers into extremely precocious foragers

Abstract: The switch from within-hive activities to foraging behavior is a major transition in the life cycle of a honeybee (Apis mellifera) worker. A prominent regulatory role in this switch has long been attributed to juvenile hormone (JH), but recent evidence also points to the yolk precursor protein vitellogenin as a major player in behavioral development. In the present study, we injected vitellogenin double-stranded RNA (dsVg) into newly emerged worker bees of Africanized genetic origin and introduced them togethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
100
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 128 publications
(110 citation statements)
references
References 44 publications
4
100
0
3
Order By: Relevance
“…Social insect queens have very high vitellogenin levels in the hemolymph (insect blood), whereas, worker vitellogenin levels are connected to task-specialization [17] . For example, in workers, the behavioral change from brood care (high vitellogenin) to foraging outside the hive or nest is preceded by a drastic drop in vitellogenin levels in the hemolymph of bee/ant workers [19,21,22] . These differences in vitellogenin levels are linked to the variation observed in the immunocompetence and life span of the distinct castes and worker types in social insects, mostly studied in the honey bee [23] .…”
Section: Research Highlightmentioning
confidence: 99%
“…Social insect queens have very high vitellogenin levels in the hemolymph (insect blood), whereas, worker vitellogenin levels are connected to task-specialization [17] . For example, in workers, the behavioral change from brood care (high vitellogenin) to foraging outside the hive or nest is preceded by a drastic drop in vitellogenin levels in the hemolymph of bee/ant workers [19,21,22] . These differences in vitellogenin levels are linked to the variation observed in the immunocompetence and life span of the distinct castes and worker types in social insects, mostly studied in the honey bee [23] .…”
Section: Research Highlightmentioning
confidence: 99%
“…qRT-PCR was performed using SYBR green (Applied Biosystems Inc., Foster City, CA) and the 7500 Fast System real-time PCR detection system following the supplier's protocol (Applied Biosystems Inc., Foster City, CA). Relative quantification of the transcripts were calculated using the comparative 2-ddCT method (Livak and Schmittgen, 2001) and were normalized to A. mellifera β-actin (Antonio et al, 2008).…”
Section: Transcriptional Validation Using Quantitative Real Time Pcrmentioning
confidence: 99%
“…Foragers preferentially consume nectar (Crailsheim et al, 1992) and a low protein diet (Slansky and Scriber, 1985). Studies made with Africanized and European honey bees have shown that workers that had the gene encoding vitellogenin silenced by RNAi made foraging flights earlier (Nelson et al, 2007;Marco Antonio et al, 2008).…”
Section: Protein Diets In Honey Beesmentioning
confidence: 99%